Pay Factors as Predictors to Satisfaction: A Comparison of Reinforcement, Equity, and Expectancy - Klein, Stuart M. (Academy of Management Journal, 1973)
A comparison of pay variables suggested by reinforcement, expectancy, and equity theories as predictors to a measure of global satisfaction is presented. Equity and expectancy variables provided predictive capabilities though equity seemed somewhat more powerful. Reinforcement provided no predictive capability by itself. A model incorporating these findings is suggested.